Entry restricted security system for a smart home - Razi, Abdullah Al; Hossain, Md. Emarat; Rahman, Farah; Shahnawaj, Md. Hossain (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.